Implementing systems thinking to manage risk in public private partnership projects. Issue 6 (August 2015) - Loosemore, M.; Cheung, E.
Abstract The complexity of public private partnership (PPP) projects ensures that risks can arise and spread in unpredictable and sometimes catastrophic ways. Systems thinking is often proposed as a potential solution to this problem but has not been widely adopted in practice. To explore the reasons for this, interviews were conducted with sixteen senior construction professionals with experience of PPPs. The results show that the main barriers to the adoption of systems thinking are: conflicts of interest within PPP projects; confrontational contracts; resistance to change; lack of time and resources; perceptions of complexity; unknown legal implications of sharing risk; and external validation of existing risk management practices. It is concluded that in moving to a systems thinking approach, deeply imbedded ontologies, path dependencies, confrontational practices, and traditional linear and reductionist risk management practices will need to be challenged. Five key questions are also proposed for future research in this area.